CARRIE SMITH and LISA STEAD, eds., The Boundaries of the Literary Archive: Reclamation and Representation - Dunks, Gillian (Archivaria, 2019)
The Boundaries of the Literary Archive: Reclamation and Representation. Carrie Smith and Lisa Stead, eds. New York: Routledge, 2013. xi, 210 pp. ISBN 978-0-8153-4658-6